Influence of intimate partner violence on the well-being of adults in ibadan metropolis (2024)
Intimate partner violence (IPV) is indeed a significant issue affecting various demographics, including adolescents. IPV encompasses any behavior within an intimate relationship that causes physical, emotional, or sexual harm to the individuals involved. The study employs a descriptive research design of correlational study. The study targets adults within Ibadan metropolis. A multi-stage sampling technique is employed, starting with purposive sampling of local Government Area, followed by random selection of 200 male and female adults. The findings of the study revealed that there is a significant positive relationship between intimate partner violence (IPV) and the physical well-being, evidenced by a correlation coefficient (r=.479, p-value <0.05). Hypothesis two revealed that a significant positive relationship between intimate partner violence (IPV) and the psychological well-being, with a correlation coefficient (r=.631, p-value <0.05. Hypothesis three revealed that positive correlation between intimate partner violence (IPV) and the social well-being, with a correlation coefficient (r= .562, p-value <0.05). The study concludes that Intimate Partner Violence (IPV) significantly impacts the overall well-being of adults, affecting them physically, psychologically, and socially. The study recommend to incorporate IPV screening and intervention into regular healthcare services and also train healthcare professionals to identify and respond effectively to IPV. Finally, ensure access to thorough medical care for both immediate injuries and long-term health impacts of IPV.